2004
DOI: 10.1002/esp.1124
|View full text |Cite
|
Sign up to set email alerts
|

The micro‐topography of the wetlands of the Okavango Delta, Botswana

Abstract: The surface of the 40 000 km 2 Okavango alluvial fan is remarkably smooth, and almost everywhere lies within two to three metres of a perfectly smooth theoretical surface. Deviations from this perfect surface give rise to islands in the Okavango wetlands. This microtopography was mapped by assigning empirical elevations to remotely sensed vegetation community classes, based on the observation that vegetation is very sensitive to small, local differences in elevation. Even though empirical, the method produces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 21 publications
0
36
0
1
Order By: Relevance
“…Gumbricht et al (2004) showed that the islands have a range of sizes that completely fit fractal behaviour, suggesting some self-organising principle for island formation. Gumbricht et al (2005) came up with an interesting explanation, which comes from yet another discipline: chemistry. The Okavango river carries very small amounts of salts, but considerable amounts of calcite and silica in solution, stemming from the Kalahari sands that it drains.…”
Section: What Is Hydrology?mentioning
confidence: 99%
“…Gumbricht et al (2004) showed that the islands have a range of sizes that completely fit fractal behaviour, suggesting some self-organising principle for island formation. Gumbricht et al (2005) came up with an interesting explanation, which comes from yet another discipline: chemistry. The Okavango river carries very small amounts of salts, but considerable amounts of calcite and silica in solution, stemming from the Kalahari sands that it drains.…”
Section: What Is Hydrology?mentioning
confidence: 99%
“…The system is large. The entire geologic alluvial fan encompasses 40 000 km 2 (Gumbricht et al, 2005) and flooding extents range from 6 000-12 000 km 2 (Wolski et al, 2006). No roads traverse the area and the field collection of data is extremely cumbersome.…”
Section: Study Sitementioning
confidence: 99%
“…Hence, the peat in these extensive wetlands is not as deep as, for instance, in the peat domes of South East Asia. Gumbricht et al (2005) developed a simple, but successful method for estimating the microtopography of Okavango wetlands on an alluvial fan in Botswana. From empirical relationships between the wetland vegetation communities and the depth of flooding, they were able to accurately estimate the surface topography of the Okavango peatlands indirectly based on the levels of the underlying minerogenic sediments.…”
Section: Wetlands Bound To Floodout Rivers and Alluvial Fansmentioning
confidence: 99%
“…From empirical relationships between the wetland vegetation communities and the depth of flooding, they were able to accurately estimate the surface topography of the Okavango peatlands indirectly based on the levels of the underlying minerogenic sediments. Thus the approach used by Gumbricht et al (2005) could be used to estimate the volumes of peat of the Okavango and similar wetlands.…”
Section: Wetlands Bound To Floodout Rivers and Alluvial Fansmentioning
confidence: 99%